Evaluation of Amoxicillin Utilization at Outpatient Department in Abebe Bikila Health Center, Addis Ketema Sub City, Addis Ababa, Ethiopia: Drug Use Evaluation Study - Ahmed, Abduselam; Agdew, Jemal; Tizazu, Alem; Regasa, Sisay; Zenebe, Dagne; menji, Tsegaye; Abera, Gosaye; Siyum, Micheal (Indian Journal of Pharmacy Practice, 2026)
Background: Amoxicillin is a widely used β-lactam antibiotic belonging to the penicillin class and is commonly prescribed for the treatment of various bacterial infections in both primary and secondary healthcare settings. However, its effectiveness is increasingly threatened by the growing global challenge of Antimicrobial Resistance (AMR). Objectives: This study aimed to assess the utilization of amoxicillin among patients attending the outpatient department of Abebe Bikila Health Center, located in Addis Ketema Sub-City, Addis Ababa, Ethiopia, in 2025. Materials and Methods: A facility-based retrospective cross-sectional study was conducted from July 1 to September 30, 2025. A total of 422 prescriptions, along with their corresponding patient charts, were randomly selected from the study period. Data were collected using the World Health Organization (WHO) drug use evaluation tool. Following data checking, cleaning, and coding, the data were analyzed using Epi Info version 3 and SPSS version 26. Descriptive statistics, including frequencies, proportions, and graphical presentations, were used to summarize the findings. Results: All 422 selected prescriptions were reviewed, yielding a response rate of 100%. The overall prevalence of appropriate amoxicillin use was 70.1% (95% CI: 65.5%-74.5%). Compliance with individual prescribing indicators was as follows: correct indication (96.0%), correct dose (92.4%), correct duration (73.0%), and correct frequency (96.9%). In addition, assessment for potential drug interactions and screening for contraindications were performed in all cases (100%). Conclusion and Recommendation: The overall prevalence of appropriate amoxicillin use in the study setting was below World Health Organization (WHO)-recommended standards. Strengthening adherence to national and WHO standard treatment guidelines is therefore essential. Regular training of prescribers on rational drug use is recommended, alongside consistent prescription review by pharmacists to ensure compliance with established guidelines.
Keywords: Addis Ketema; Amoxicillin; Drug Use Evaluation; Ethiopia; Rational Drug Use